2017
DOI: 10.1111/sdi.12658
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of hemodialysis vascular access failure and systemic therapies for its prevention: Optimism unfulfilled

Abstract: In patients receiving hemodialysis, the provision of safe and effective vascular access using an arteriovenous fistula or graft is regarded as a critical priority by patients and health professionals. Vascular access failure is associated with morbidity and mortality, such that strategies to prevent these outcomes are essential. Inadequate vascular remodeling and neointimal hyperplasia resulting in stenosis and frequently thrombosis are critical to the pathogenesis of access failure. Systemic medical therapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 106 publications
(235 reference statements)
1
67
0
4
Order By: Relevance
“…The pathogenesis of vascular access failure is complex with the common final pathway being the combination of insufficient vessel vasodilation, negative (inward) vascular remodeling and neointimal hyperplasia resulting in luminal narrowing and often associated thrombosis formation. The Achilles heel of this process is the graft-vein anastomosis in AVG and the perianastomotic region in AVF, respectively [1,13]. The pathophysiologic cascade of events that lead to AVF and AVG failure [16,17] have been categorized into upstream events, characterized by factors that lead to injury of endothelial-and smooth muscle cells and downstream events describing the cellular and cytokine responses that leads to neointimal hyperplasia and inward remodeling [16] (Figure 1).…”
Section: Pathophysiology Of Arteriovenous Access Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathogenesis of vascular access failure is complex with the common final pathway being the combination of insufficient vessel vasodilation, negative (inward) vascular remodeling and neointimal hyperplasia resulting in luminal narrowing and often associated thrombosis formation. The Achilles heel of this process is the graft-vein anastomosis in AVG and the perianastomotic region in AVF, respectively [1,13]. The pathophysiologic cascade of events that lead to AVF and AVG failure [16,17] have been categorized into upstream events, characterized by factors that lead to injury of endothelial-and smooth muscle cells and downstream events describing the cellular and cytokine responses that leads to neointimal hyperplasia and inward remodeling [16] (Figure 1).…”
Section: Pathophysiology Of Arteriovenous Access Dysfunctionmentioning
confidence: 99%
“…Aspirin irreversibly inhibits platelet cyclooxygenase-1 and -2 enzymes via acetylation, resulting in decreased formation of prostaglandin precursors and prostaglandin derivative thromboxane A2 [13]. Randomized controlled trials (RCT) on the efficacy of aspirin in preventing arteriovenous access failure have shown inconsistent results, with two small studies favoring aspirin [67,68] and two studies showing no significant treatment benefit for the prevention of arteriovenous access thrombosis and failure (Table 1) [5,69].…”
Section: Aspirinmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend is echoed by others 18,[28][29][30][31] and has contributed in the shift from forearm to upper-arm AV accesses predominantly in the US 32 . Patients with previous failed AV access are susceptible to future AV access failure and this is conceivably related to the presence of pre-existing risk factors for failure or the occurrence of maladaptive vascular remodelling and neointimal hyperplasia following creation of the previous failed AV access 33 .Brachial-cephalic AV accesses had better patency rates compared to brachial-basilic and this is opposed to previous studies which have shown less primary failures for basilic vein AV accesses and similar cumulative access survival [34][35][36] . This finding should be interpreted with caution and may merely represent the practice of rarely using the basilic vein as a first option and thus the majority of these AV accesses were created in patients with previous failed VA procedures or poor cephalic options hence were representative of a cohort of patients with difficulties in establishing permanent access.…”
Section: Discussionmentioning
confidence: 73%
“…In addition to exploring treatments to improve vascular access function, further research is Given the complexity of AVF failure outlined at the beginning of this thesis, it is unlikely that a single intervention will suffice to achieve a clinically meaningful improvement in AVF outcomes. Instead, combining different interventions that target sequential events in the pathogenesis of arteriovenous access failure may be more effective 257 . In particular, the combination of interventions that target both the upstream "injury pathways" (e.g.…”
Section: Exploration Of Mechanistic Pathways Of Avf Failurementioning
confidence: 99%